Short-term herding of institutional traders: New evidence from the German stock market - Stephanie Kremer; Dieter Nautz (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2011)
This paper employs a new and comprehensive data set to investigate short-term herding behavior of institutional investors. Using data of all transactions made by financial institutions in the German stock market, we show that herding behavior occurs on a daily basis. However, in contrast to longer-term herding measures obtained from quarterly data, results based on daily data do not indicate that short-term herding tends to be more pronounced in small capitalized stocks or in times of market stress. Moreover, we find that herding measures based on anony- mous transactions can lead to misleading results about the behavior of institutional investors during the recent financial crisis.
Keywords: D81; G11; G24; 330; herding; investor behavior; institutional trading; anonymous transaction data; Institutioneller Anleger; Anlageverhalten; Herdenverhalten; Aktienmarkt; Deutschland